PERAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI UPAYA MENINGKATKAN DISIPLIN KERJA GURU DAN STAFF DI SEKOLAH - Langga Budi Prasetya, Air; Nashrullah, Mochamad; Rindanigsih, Ida (Antis Publisher, 2023)
Due to the era of globalization and the ever-increasing level of competition in the education sector, the leadership of the principal plays a crucial role in maintaining effective teacher work discipline. The principal ought to pay more attention to the teacher's labor discipline because this is an ongoing issue. The principal must possess a strong spirit of leadership in order to effectively discipline teachers who fail to perform their duties. The goals of the study that was done are as follows: 1) comprehending the principal's leadership role in enhancing teacher and employee work discipline; 2) being aware of the challenges the principal faces in enhancing teacher and employee work discipline. This study employs a subjective engagement methodology and a writing survey technique to select information from books, journals, and articles related to the subject under investigation. The review reveals that the principal's responsibility for further developing the work discipline of educators and education personnel consistently fosters a sense of responsibility, particularly as a pioneer, superintendent, and inspiration in the school climate. The principal's role in enhancing teacher discipline is determined by the leadership style and strategy they employ. The inability to communicate effectively with teachers and other staff members presents a challenge that principals frequently encounter when attempting to enhance teacher and staff work discipline